KATAK SEBAGAI OBJEK UTAMA DALAM KARYA SENI KERAMIK - DESRI YULIANTI, Dra. Jupriani, M.Sn., Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2017)
The purpose of this artworks is to show the beauty of the form of frogs in ceramic. Furthermore the artwork take the funny and unique character from this frogs. then, the artwork put the bright colors and give the florals into this artworks. The ceramis made into three dimensional artworks. The theme of this artworks is the human mind pattern which is develop forward (positive thingking). The title of this ceramic artworks are: First, “Jumping”. Second, “The story of three frogs”. Third, “The horde of frogs”. Fourth, “Dreaming”. Fifth, “Mother’s Hope”. Sixth, “Casper”. Seventh. “Protector”. Eight, “Confidence”.Kata Kunci: Katak, Keramik